Macroporous Superhydrophobic Coatings with Switchable Wettability Enabled by Smart Shape Memory Polymers. Issue 13 (7th March 2021) - Leverant, Calen J.; Zhang, Yifan; Cordoba, Maria A.; Leo, Sin‐Yen; Charpota, Nilesh; Taylor, Curtis; Jiang, Peng
Abstract: Here, a facile bottom‐up nanofabrication technology for making smart superhydrophobic coatings with switchable wettability and tunable optical properties by integrating shape memory polymers (SMPs) with templated macroporous photonic crystals is reported. Thermoresponsive shape memory efforts exhibited by a polyurethane‐based shape memory copolymer enable reversible microstructural transitions between a "memorized" permanent configuration composing of highly ordered arrays of macropores and a temporary deformed structure with collapsed macropores. The unique macroporous SMP photonic crystal arrays with large surface roughness can entrap a large portion of air in the interconnecting macropores, resulting in superior superhydrophobic properties including high apparent water contact angle (CA > 160°) and low CA hysteresis. Importantly, the shape memory‐enabled microstructural transitions lead to drastic wettability switching from superhydrophobic (CA > 160°) to hydrophobic (CA ≈ 110°) or from oleophobic (CA ≈139° for hexadecane) to oleophilic (CA ≈ 80°). The large CA tunability (>50°) coupled with the simultaneous color change from shining iridescence to colorless associated with the same microstructural transition can not only provide a noninvasive means for visually indicating the surface wetting states, this favorable coupling between the wetting and optical behaviors of macroporous SMP photonic crystal membranes can also pave the way for developing new tunable nanooptical devices. Abstract : Smart superhydrophobic coatings with switchable wettability and tunable optical properties have been developed by integrating shape memory polymers with templated macroporous photonic crystals. The thermoresponsive microstructural transitions between a "memorized" ordered configuration and a temporary deformed state enable easily perceived structural color change coupled with reversible wettability switching between superhydrophobicity and hydrophobicity or oleophobicity and oleophilicity with drastic contact angle change.